2024
DOI: 10.1037/cfp0000233
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive meta-analysis on the efficacy of emotionally focused couple therapy.

Abstract: Emotionally Focused Couple Therapy (EFT), as developed by Greenberg and Johnson (1988) and Johnson (1996Johnson ( , 2004Johnson ( , 2020, is an evidence-based treatment that works with a variety of presenting concerns (e.g., depression, posttraumatic stress disorder, sexual dissatisfaction) and treatment characteristics, with good maintenance of treatment gains up to 2 years following treatment. In this first comprehensive meta-analysis of EFT, we evaluated the entirety of efficacy outcome research including r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…It emphasises that a strong therapeutic relationship is essential in facilitating the ongoing therapeutic process (Greenberg & Johnson, 1988). In a meta-analysis of 20 studies detailing the efficacy of EFT, Spengler et al (2022) found that EFT was an effective, evidence-based treatment for presenting concerns such as depression, sexual dissatisfaction and PTSD. This does not provide a specific modality that therapists are required to follow during integration sessions; however, the author suggests that the therapist should not be married to any one theory (Wolfson, 2022).…”
Section: Emotionally Focused Couples Therapymentioning
confidence: 99%
“…It emphasises that a strong therapeutic relationship is essential in facilitating the ongoing therapeutic process (Greenberg & Johnson, 1988). In a meta-analysis of 20 studies detailing the efficacy of EFT, Spengler et al (2022) found that EFT was an effective, evidence-based treatment for presenting concerns such as depression, sexual dissatisfaction and PTSD. This does not provide a specific modality that therapists are required to follow during integration sessions; however, the author suggests that the therapist should not be married to any one theory (Wolfson, 2022).…”
Section: Emotionally Focused Couples Therapymentioning
confidence: 99%
“…EFT (Johnson, 2019; Johnson & Greenberg, 1985b) is an empirically supported treatment for relationship distress (Spengler et al, 2022). EFT posits distress results from iterative restrictive emotional responses which reinforce patterns of disconnection (Johnson, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…EFT is a strong model for working with polyamorous relationships for several reasons. Primarily, EFT has a strong research base (Beasley & Ager, 2019; Spengler et al, 2022) and the dedication of EFT practitioners to conceptualizing multicultural work within the model (e.g., Allan et al, 2022; Guillory, 2021; Nightingale et al, 2019; Soleimani et al, 2015; Tseng, 2022) signifies the application of the model across contexts and cultures. In addition, the non‐pathologizing nature of EFT, its roots in systems theory and attachment theory provide a secure base for treating polycules.…”
Section: Emotionally Focused Therapy With Clients In a Polyamorous Re...mentioning
confidence: 99%
“…A meta‐analysis of 20 studies of EFT with 332 couples found medium to large treatment effects for relationship distress from pretest to posttest and pretest to follow‐up (Spengler et al, 2022). It also found medium to large treatment effects for EFT versus alternative couple interventions.…”
Section: Emotionally Focused Therapymentioning
confidence: 99%